The infraorbital artery: From descriptive anatomy to mucosal perforator flap design. Issue 7 (25th January 2019) - Hufschmidt, Katharina; Camuzard, Olivier; Balaguer, Thierry; Baqué, Patrick; de Peretti, Fernand; Santini, Joseph; Bronsard, Nicolas; Qassemyar, Quentin
Abstract: Background: The terminal and perforating branches of the infraorbital artery (IOA) are poorly described. Its anatomical situation and mucosal component could provide an interesting donor site for mucosal reconstruction. The aims of the following study were to establish an anatomical description and to assess the feasibility of mucosal perforator flaps for eyelid and nasal reconstruction. Methods: Twenty‐three fresh cadaver hemifaces were studied in order to perform an IOA anatomical classification by recording the artery's characteristics, its course, number, type, and diameter of terminal branches. We also examined the feasibility of local flaps for facial reconstruction. Results: We highlighted five different types of courses. All cadavers had at least one superior vestibular branch with a caliber of ≥0.4 mm. A pedicled flap arising from the vestibular branch was raised in all dissections. Conclusion: The vestibular perforator flap based on the IOA seems to be a reliable flap in reconstruction of mucosal defects.